Little School on the Prairie: School District Records at the Provincial Archives of Alberta - Cook, Kristan (Archivaria, 2009)
This paper explores topics pertaining to school district records held at the Provincial Archives of Alberta (PAA). The first section discusses how provincial legistation created school districts, and modified the administration and governance of school districts. The second section examines the way in which these changes to the administration and governance influenced who donated school district records to the PAA and what kinds of records are included in these acquistions. Lastly the paper analyzes how provincial Freedom of Information and Protection and Privacy legislation governs access to school district records at the PAA. Ultimately, the paper urgues archivists to educate themselves and their patrons about legislation to improve patron satisfaction. RÉSUMÉ Ce texte présente des sujets liés aux documents de districts scolaires qui sont conservés aux Provincial Archives of Alberta (PAA). La première partie examine les façons dont la législation provinciale a créé les districts scolaires et modifié leur administration et leur gouvernance. La deuxième partie explore la façon dont ces changements ont eu une incidence sur les personnes qui ont versé des documents des districts scolaires aux PAA, ainsi que sur le genre de documents inclus dans ces versements. Enfin, ce texte fait l’analyse de la loi provinciale sur la Freedom of Information and Protection and Privacy [Liberté de l’information et protection et vie privée] et montre comment cette législation gouverne l’accès aux documents des districts scolaires qui sont conservés aux PAA. En fin de compte, ce texte encourage les archivistes à se renseigner au sujet de cette législation et à diffuser cette information à leur clientèle, afin d’améliorer la satisfaction de ceux qui fréquentent les archives.